Analysis of water quality in the watershed Brazilian semiarid - Silva, Viviane Farias; Pessoa, Dihego Souza; Lima, Thalis Leandro Bezerra; Cosme, Ana Maria Ferreira; Lima, Vera Lucia Antunes (Ciência e Natura, 2018)
Water is a renewable natural resource, important for maintenance of life on the entire planet. Even with this significance is a feature that has been degraded and reduced the quality to use. In the Brazilian semi-arid region water scarcity by influencing the quality of life of the population, directly affecting the socio-economic and development means. In this context, the present research was conducted aiming to evaluate the water quality in the watershed Brazilian semiarid. The survey was conducted in three watersheds (Capibaribe river, Ipojuca river and Igarassu river) in the State of Pernambuco, Brazil. Water Quality Index (WQI) and Biochemical Oxygen Demand (BOD) annual averages of the year 2006 to 2015. In Capibaribe river watershed the largest concentrations of BOD occurred in 213, 2014 and 2015, with average was 4.95 mg/L. By increasing the BOD value there is a reduction of WQI. The Igarassu river, it was verified that from 2006 to 2014 the hydrographic basin has water quality classified as good. The BOD in the waters of the Ipojuca river has little influence on the water quality index.There is a degradation on the quality of water of basins due mainly to anthropic pollution.